Prognosis Implication of N-Terminal Pro-B-Type Natriuretic Peptide in Adult Patients With Acute Myocarditis - Zhao, Yan; Lyu, Naqiang; Zhang, Wei; Tan, Huiqiong; Jin, Qi; Dang, Aimin (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aims to investigate the role of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in predicting the poor prognosis of adult patients with acute myocarditis. Methods: A total of 170 adult patients with available NT-proBNP data were included in the study. They were divided into four groups according to quartiles of NT-proBNP levels. Baseline and follow-up information was collected. 30-day major adverse cardiac events (MACE) were death and heart transplantation. Long-term MACE included all-cause death, heart transplantation, heart failure requiring re-hospitalization, sustained ventricular arrhythmia, and myocarditis relapse. Results: During a median follow-up of 3.8 years, patients in the highest NT-proBNP quartile suffered from the highest risk both of 30-day and long-term MACE (P<0.001 by log-rank test). Multivariate analysis showed that apart from left ventricular ejection fraction (LVEF), an increased baseline NT-proBNP > 3549pg/ml (hazard ratio 3.533, 95% CI 1.381-9.037, P = 0.008) and > 7209 pg/ml (hazard ratio 13.058, 95% CI 1.989-85.737, P = 0.007) was independent predictor of long-term and 30-day MACE, respectively. Conclusions: Higher baseline NT-proBNP level was a strong predictor of poor prognosis in adult patients with acute myocarditis. Therefore NT-proBNP may serve as a useful biomarker for risk stratification in acute myocarditis patients.